In what ways does age-differentiated leadership influence employee health? - Lena Marie Uhlmann; Tina Karabinski; Johannes Wendsche; Jürgen Wegge (Zeitschrift für Arbeitswissenschaft, 2023)
According to Wegge et~al. ( 24 ), leadership behavior can affect employee health in several ways. The model describes leaders (1)~as actors with a~direct influence on the health of employees, (2)~as designers of work systems, (3)~as a~moderating factor (buffer/amplifier) of the effects of work requirements and resources on health, (4)~as a~developer of group climate and identification and (5)~as direct role models for health-related behavior. In order to collect evidence for the usefulness of this multi-path model, connections between age-differentiated leadership (ADL) and health were analyzed in 947~employees of a~German technology company. ADL is a~management style that takes into account the particularities of mixed-age teams and also differentiates between the different needs of different age groups. It was found that better ADL (when controlling for employee-oriented leadership) is associated with fewer physical and psychological complaints (pathway~1). This relationship is mediated by the manager's social support (path~2) and a~better recreational climate in the team (path~4). Better ADL also reduced the negative effects of psychological work demands on the psychological symptoms (pathway~3). Practical Relevance : This article provides practical evidence for the multi-way model of leadership and health. Using the example of age-differentiated leadership (ADL)—with control of employee-oriented leadership—it was also found that this leadership behavior has a~positive effect on the mental and physical health of employees via four different paths and should therefore be encouraged.
Keywords: 650; Health; Age-differentiated leadership; Recovery climate; Gesundheit; Alter(n)sgerechte Führung; Erholungsklima